2007
DOI: 10.1111/j.1095-8649.2007.01638.x
|View full text |Cite
|
Sign up to set email alerts
|

Rate of energy depletion and overwintering mortality of juvenile walleye pollock in cold water

Abstract: The winter energy deficit and mortality of juvenile walleye pollock at extremely cold temperature were examined by field observations and laboratory experiments. In the Doto area, along the northern coast of Japan, juvenile walleye pollock resided on the continental shelf despite extremely cold temperatures (mean 0Á4°C) during the latter half of winter (March to April). Measurements of the rate of energy depletion (equivalent to the routine metabolic rate) revealed that juvenile walleye pollock consumed 37% le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
0
12
1
Order By: Relevance
“…Juvenile pollock in the low-lipid treatment consumed mainly protein throughout the experiment. In the high-lipid treatment, cumulative starvation mortality was 1.6% after the first period and 19.1% after the second period, whereas in the low-lipid treatment, mortality rates were 28.8% and 74.5% after the first and second periods, respectively (Kooka et al 2007a). The low-lipid fish likely entered the terminal adaptation phase during the second period, as this phase ultimately leads to mass mortality (Castellini and Rea 1992;Gibney et al 2003).…”
Section: Sequential Phases In Metabolism During Starvationmentioning
confidence: 92%
See 1 more Smart Citation
“…Juvenile pollock in the low-lipid treatment consumed mainly protein throughout the experiment. In the high-lipid treatment, cumulative starvation mortality was 1.6% after the first period and 19.1% after the second period, whereas in the low-lipid treatment, mortality rates were 28.8% and 74.5% after the first and second periods, respectively (Kooka et al 2007a). The low-lipid fish likely entered the terminal adaptation phase during the second period, as this phase ultimately leads to mass mortality (Castellini and Rea 1992;Gibney et al 2003).…”
Section: Sequential Phases In Metabolism During Starvationmentioning
confidence: 92%
“…The lipid contents of (Paul 1986) and energy equivalents (4.63×10 −3 cal μl −1 O 2 and 4.1855 Jcal −1 ). These values are adjusted to the body mass and ambient water temperatures in the field b Mobilizable energy [(total energy of field fish)-(total energy of mortalities)] divided by daily energy expenditure c Wet mass and lipid and protein energy are adjusted to a 126-mm fish mortalities were mostly <1% in the starvation experiment, but in the low-lipid treatment, >70% of starved fish were capable of surviving by day 35 (Kooka et al 2007a) despite the lower lipid level. The mobilizable energy (i.e.…”
Section: Seasonal Energy Allocation and Deficitmentioning
confidence: 99%
“…house sparrow Passer domesticus), fishes (i.e. walleye pollock Theragra chalcogramma), and red deer Cervus elaphus, die during the onset of spring when prey availability is low and environmental over-wintering stress is high (Guinness et al 1978, Johnston & Fleischer 1981, Kooka et al 2007). …”
Section: Sooty Shearwatersmentioning
confidence: 99%
“…Winter water temperatures in the bottom layer generally ranged from 0 to 3° C in the shelf area, whereas they were 2 to 5° C in the slope area (Kasai et al ., 2001; Shida et al ., 2008; present study). Juveniles reared at 0·5° C were able to conserve 37% of the energy consumed at 2·0° C under a starvation condition (Kooka et al ., 2007). Therefore, it is suggested that juvenile T. chalcogramma on the shelf survive winter without high pre‐winter lipid storage because occasional feeding in the cold shelf water benefits energy conservation.…”
Section: Discussionmentioning
confidence: 99%